2019
DOI: 10.1038/s41598-019-46490-4
|View full text |Cite
|
Sign up to set email alerts
|

Photobiomodulation (660 nm) therapy reduces oxidative stress and induces BDNF expression in the hippocampus

Abstract: Photobiomodulation therapy (PBMT) effects an important role in neural regeneration and function enhancement, such as expression of nerve growth factor and nerve regeneration, in neuronal tissues, and inhibition of cell death by amyloid beta in neurons is inhibited by PBMT. However, there no studies evaluated the effects of PBMT on oxidative stress in the hippocampus. The aim of this study is to evaluate the effects of PBMT on oxidative stress in the hippocampus. This study assessed the anti-oxidative effect, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(46 citation statements)
references
References 33 publications
2
40
0
Order By: Relevance
“…FR/ NIR photons are absorbed by the mitochondrial photoacceptor molecule, CcO, triggering intracellular signaling pathways that culminate in improved mitochondrial energy metabolism, increased cytoprotective factor production, and cell survival. FR/NIR PBM improves healing outcomes demonstrated by increasing fibroblast proliferation, synthesis of collagen and procollagen, angiogenesis, and upregulating macrophage and lymphocyte function (53,54). In this study, our custom-designed non-contact noninvasive fluorescence imager detects the wound healing trajectory after FR irradiation by monitoring the online mitochondrial metabolic state quantitatively.…”
Section: Discussionmentioning
confidence: 99%
“…FR/ NIR photons are absorbed by the mitochondrial photoacceptor molecule, CcO, triggering intracellular signaling pathways that culminate in improved mitochondrial energy metabolism, increased cytoprotective factor production, and cell survival. FR/NIR PBM improves healing outcomes demonstrated by increasing fibroblast proliferation, synthesis of collagen and procollagen, angiogenesis, and upregulating macrophage and lymphocyte function (53,54). In this study, our custom-designed non-contact noninvasive fluorescence imager detects the wound healing trajectory after FR irradiation by monitoring the online mitochondrial metabolic state quantitatively.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have shown that PBM rescues dendritic atrophy in Alzheimer’s disease by upregulating brain-derived neurotrophic factor (BDNF) [ 18 ]. In the case of 660-nanometer PBM, it reduces oxidative stress and induces BDNF expression in the hippocampus [ 19 ]. Furthermore, PBM regulates microglial function in neurodegenerative diseases [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…The transcription of BDNF can be activated by Ca 2+ influx and Ca 2+ -dependent activation of ERK and cAMP/ PKA pathways (Zheng et al 2012). The BDNF upregulation through Ras/ERK and binding of phosphorylated CREB to BDNF promoter was confirmed by the above-mentioned study in Alzheimer's disease model and in another study of hippocampal neurons under oxidative stress (Meng et al 2013;Heo et al 2019). Glial cell line-derived neurotrophic factor (GDNF) was also found to be upregulated by PBM in monkey models of Parkinson's disease (El Massri et al 2017).…”
Section: Maintenance and Activity Of Neuronsmentioning
confidence: 65%
“…PBM is known to activate multiple pathways such as ERK/ CREB (Meng et al 2013;Gu et al 2017;Heo et al 2019), cAMP/PKA/SIRT1 (Zhang et al 2020), PKC (Zhang et al 2008), Src/Syk/PI3K/Akt (Song et al 2012), and Akt/ GSK3β/β-catenin (Liang et al 2012), involved in various molecular networks in the cellular system. From the data, three significant paths through which the above-mentioned signaling cascades might be activated after PBM by CCO stimulation could be identified as follows:…”
Section: Mitochondrial Stimulation Triggers Several Signaling Pathwaysmentioning
confidence: 99%